Effectiveness of interactive voice response-call for life mHealth tool on adherence to anti-retroviral therapy among young people living with HIV: A randomized trial in Uganda. - Agnes Bwanika Naggirinya; David B Meya; Maria Sarah Nabaggala; Grace Banturaki; Agnes Kiragga; Joseph Rujumba; Peter Waiswa; Rosalind Parkes-Ratanshi (PLoS ONE)
Introduction In people living with HIV, adherence to antiretroviral therapy (ART) is essential for achieving and sustaining viral suppression and reducing mortality. In young people living with HIV, ART adherence and retention remain a challenge with unsatisfactory viral suppression rates despite facility-based intensive adherence counseling that is the standard of care. Few studies have evaluated mHealth adherence interventions among young people living with HIV in resource-limited settings. Methods This was a randomized parallel trial. Young people aged between15-24 living with HIV, initiating ART, or on ART for not more than 6 months at three ART clinics were recruited and randomized to a ratio of 1:1 to either standard of care or the intervention "Call for Life-Interactive Voice Response" with standard of care, between 12th August 2020 and 1st June 2022. The intervention is mobile technology-based software, that has interactive voice response functionalities, with a web-based interface, that allows interaction through the use of voice and tones via a dial pad. The primary outcome was viral suppression defined as HIV RNA below 1,000 copies per mL at 12 months with retention in care and viral suppression at month 6 as a secondary outcome. Descriptive statistics were used for participant characteristics. Primary outcomes and factors associated with viral load failure were assessed using the log-binomial model. All calculations were done using statistical software release 16.0. Results A total of 206 participants were recruited and randomized; the mean age was 22.5(SD±1.9) years and 81% (167/206) were female. The intervention had 78.6% (81/103), females, while the standard of care had 83.5% (86/103). Viral suppression at 12 months in the intervention arm was 73.6% (67/91) versus 51.9% (40/77) in the standard of care arm, p=0.01. Retention in care was 88.4% (91/103) in the intervention vs. 74.7% (77/103) in the standard of care arm p=0.01. Conclusion This is the first study in Uganda to demonstrate that mHealth has the potential to improve medication adherence and retention in care among youth living with HIV in Uganda. Trial registration NCT04718974 Registry: clinical Trials.gov.